1983
DOI: 10.2172/5679191
|View full text |Cite
|
Sign up to set email alerts
|

Fire-protection research for DOE facilities: FY 82 year-end report

Abstract: We summarize our research in FY 82 for the DOE-sponsored project, Fire Protection Research for DOE Facilities. This research program was initiated in 1977 to advance fireprotection strategies for energy technology facilities to keep abreast of the unique fire problems that develop along with energy technology research. Since 1977, the program has broadened its original scope, as reflected in previous year-end reports. We are develop ing an analytical methodology through detailed study of fusion energy experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The main findings were as follows: 80± 5% of the heat produced in the fire was deposited in the enclosure walls; "quasisteady state" was not reached until about 2000 s (seconds) after ignition; and twice the stoichiometrically required ventilation was needed to ensure complete combustion of the fuel in a low-inlet, forced-ventilation geometry. Further tests (Alvares et al, 1984) confirmed and refined these observations, providing data that was used to develop a temperature correlation for forced-ventilation compartment fires (Foote et al, 1986) and tc test and compare available computer fire models (Hasegawa et al, 1984, andCox et a1., 1986). This paper is based on the 1986 series of 64 tests in which the effects of ventilation rate, ventilation configuration, fire elevation, and enclosure geometry were examined using methane gas fires.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The main findings were as follows: 80± 5% of the heat produced in the fire was deposited in the enclosure walls; "quasisteady state" was not reached until about 2000 s (seconds) after ignition; and twice the stoichiometrically required ventilation was needed to ensure complete combustion of the fuel in a low-inlet, forced-ventilation geometry. Further tests (Alvares et al, 1984) confirmed and refined these observations, providing data that was used to develop a temperature correlation for forced-ventilation compartment fires (Foote et al, 1986) and tc test and compare available computer fire models (Hasegawa et al, 1984, andCox et a1., 1986). This paper is based on the 1986 series of 64 tests in which the effects of ventilation rate, ventilation configuration, fire elevation, and enclosure geometry were examined using methane gas fires.…”
Section: Introductionmentioning
confidence: 83%
“…Since 1981, a program to investigate forced-ventilation fires has been conducted using the Fire Test Cell at Lawrence Livermore National Laboratory (LLNL). The early experiments (Hasegawa et al, 1983) used a variety of fuels, ventilation rates, and fire strengths (heat release rates). Most of these fires were analog pool fires in which gas fuel was metered into a burner.…”
Section: Introductionmentioning
confidence: 99%
“…The test is terminated when the flame has spread up the entire cable, or when it becomes clear that the flame will no longer propagate. Some aspects of this test procedure, in particular the preheating times, were established to duplicate the conditions in large-scale vertical panel tests conducted previously at LLNL [4]. In this procedure the pilot flame used for ignition is in contact with the cable jacket from the time that the surface reaches lOOoe until ignition is observed.…”
Section: Methodsmentioning
confidence: 99%
“…Interest in predicting tire behavior of these materials encouraged research aimed at assessing their fire risk [1][2][3][4][5][6][7]. Indeed, current industrial standards generally rate cable flammability relative to the performance of some reference material exposed to a specific fire source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation